Design of tomato fruits with reduced allergenicity by dsRNAi-mediated inhibition of ns-LTP (Lyc e 3) expression - Sonnewald, Uwe; et al. (Plant Biotechnology Journal, 2006)
Plant genetic engineering has the potential to introduce new allergenic proteins into foods but, at the same time, it can be used to remove established allergens. Here, we report the molecular characterization of Lyc e 3, a new tomato (Lycopersicon esculentum) allergen, and the efficient down-regulation of its expression in transgenic tomato plants. Following the identification of an immunoglobulin E (IgE)-binding 9-kDa polypeptide in tomato peel, designated Lyc e 3, its partial amino acid sequence was determined by N-terminal protein sequencing. Sequence comparison revealed that Lyc e 3 encodes a nonspecific lipid transfer protein (ns-LTP). In plants, ns-LTPs are encoded by large gene families which differ in primary amino acid sequence, expression and proposed cellular function. To identify Lyc e 3 encoding complementary DNAs (cDNAs), public tomato expressed sequence tag (EST) databases were screened for ns-LTP sequences. Following this strategy, two cDNAs, LTPG1 and LTPG2, with high homology to the N-terminal sequence of Lyc e 3, were identified. Ectopic expression of LTPG1 and LTPG2 in Escherichia coli, followed by immunoblotting, verified their IgE reactivity. Subsequently, transgenic tomato plants constitutively expressing LTPG1- or LTPG2-specific double-stranded RNA interference (dsRNAi) constructs were created and tested for the suppression of Lyc e 3 accumulation. Efficient silencing of Lyc e 3 was documented by Northern and Western blotting. In both cases, Lyc e 3 accumulation was decreased to levels below the detection limit (less than 0.5% of the wild-type protein). The allergenic potential of Lyc e 3-deficient tomato fruits was tested by measuring histamine release from sensitized human basophils stimulated with transgenic and parental lines. These assays revealed a strong (10- to 100-fold) decrease in histamine release of human basophils challenged with transgenic fruit extracts when compared with control extracts. These results demonstrate the feasibility of creating low allergenic tomato fruits by means of dsRNAi inhibition.
Keywords: allergens; dsRNAi; Lyc e 3; ns-LTP; transgenic tomato